1994
DOI: 10.1212/wnl.44.10.1856
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term thalamic stimulation in Parkinson's disease

Abstract: Parkinsonian tremor may be suppressed by thalamic stimulation. For an equivalent clinical efficacy, its obvious advantage over micro-thalamotomy is its reversibility. This patient experienced postural tremor at the age of 44 years and akineto-rigid syndrome 8 years later. At the age of 60 years, intrathalamic stimulation was applied over a long-term period of 43 months until death and was efficient on tremor with low stimulation. This case is the first with anatomic verification. The extent of the lesion provo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 0 publications
6
57
0
1
Order By: Relevance
“…Similar observations have been made in postmortem studies performed after ventralis intermedius stimulation [12,18].…”
Section: Introductionsupporting
confidence: 87%
“…Similar observations have been made in postmortem studies performed after ventralis intermedius stimulation [12,18].…”
Section: Introductionsupporting
confidence: 87%
“…A strong argument in favor of a contribution of the cerebellum and its projections to the thalamus in the pathogenesis of rest tremor comes from experience with stereotactic surgery. The thalamic targets, Vim [5,10,44,46,47] and the cerebello-thalamic projections [11], have proven efficacious in the suppression of rest tremor and Vim was even postulated to a better target than the ventro-oralis posterior nucleus (Vop) receiving pallidal afferents [61]. The fact that Vim receives cerebellar afferents, but none from the basal ganglia [34], implies that rest tremor originates from either a cerebellar generator [61] or an interaction of the basal ganglia-and cerebellothalamo-cortical circuits in the cerebral cortex, where those segregated circuits converge [16].…”
Section: Discussionmentioning
confidence: 99%
“…No damage attributable to stimulation was observed. 45 The real advantage of DBS of the thalamus becomes apparent when bilateral procedures are employed. Bilateral thalamotomies have a complication rate of up to 25%.…”
Section: Dbs Of the Vim Nucleus Of The Thalamus Indications And Techmentioning
confidence: 99%
“…14, Of the 38 articles identified for DBS of the thalamus, 16 articles met criteria. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] The review of DBS of the globus pallidus consisted of all 10 articles identified, [56][57][58][59][60][61][62][63][64][65] and DBS of the subthalamic nucleus was based on all 6 articles identified. 62,[66][67][68][69][70] There were 52 articles for adrenal medullary transplantation, but the review includes only the 9 that met criteria.…”
mentioning
confidence: 99%